Higher Comorbidity Burden Predicts Worsening Neurocognitive Trajectories in People with Human Immunodeficiency Virus. (30th July 2021) - Ellis, Ronald J; Paolillo, Emily; Saloner, Rowan; Heaton, Robert K
Abstract: Background: Age-related comorbidities accumulate faster in people with HIV (PWH) than in those without HIV. We evaluated whether a validated multimorbidity scale, the Charlson index, predicted neurocognitive trajectories in PWH. Methods: Scaled scores of a comprehensive neuropsychological battery were averaged across all visits. Multilevel modeling examined between- and within-person predictors of global neurocognition. At the between-person level, averaged Charlson scores were examined as a predictor of neurocognitive change rate, covarying for HIV disease characteristics. Within-persons, visit-specific Charlson index was used to predict fluctuations in global neurocognition at the same and next visit, covarying for disease measures. Results: Participants were 1195 PWH (mean baseline age: 43.0; SD: 9.7 years) followed for a mean of 7.1 years (range: 0.5–20.5). At the between-person level, more rapid neurocognitive worsening correlated with higher (worse) average Charlson scores (standardized β: −0.062; SE: 0.015; P = .001) and lower CD4 nadir (standardized β: 0.055; SE: 0.021; P = .011), but not viral suppression or average CD4+ lymphocytes ( P > .05). At the within-person level, poorer visit-specific neurocognition was related to worse concurrent, but not preceding, Charlson scores (standardized β: −0.046; SE: 0.015; P = .003), detectable HIV viral load (standardized β: 0.018; SE: 0.006; P = .001), and higher CD4+ (standardized β: 0.043; SE: 0.009; P < .001). Conclusions: The impact of comorbidities on neurocognitive decline exceeded that of HIV disease factors. Although correlative, the temporal relationships suggested that treatment of comorbidities might improve neurocognitive prognosis for PWH. Abstract : Medical multimorbidities in this cohort of people with human immunodeficiency virus (PWH) accumulated at a high rate and were strongly associated with faster rates of neurocognitive decline. Findings suggest that interventions to prevent or ameliorate comorbidities may improve neurocognitive prognosis for PWH.